Transition from mandatory to discretionary nurse-measured MEWS assessment in a continuously monitored surgical ward: Diagnostic performance of wearable-derived early warning scores - EE Jerry; MA Afonso; JC De Vries; A Akkermans; S Turco; AR Bouwman; SW Nienhuijs (Journal of Clinical Monitoring and Computing, 2026)
Abstract Early detection of clinical deterioration on surgical wards is vital to prevent adverse outcomes. Conventional ward monitoring using the Modified Early Warning Score (MEWS) relies on intermittent nurse-measured vital signs, but its role may change when continuous wearable monitoring is already available. This study evaluated the transition from mandatory to discretionary nurse-measured MEWS assessment in a continuously monitored surgical ward and compared the diagnostic performance of two wearable-derived Early Warning Scores (EWS) with conventional MEWS. In this single-center cohort study conducted between October 2024 and June 2025, postoperative patients were continuously monitored using a wearable sensor measuring heart rate, respiratory rate, and oxygen saturation. Continuous wearable monitoring was available throughout the entire study period. During Phase 1, nurse-measured MEWS assessments were mandatory according to local protocol. During Phase 2, nurse-measured MEWS assessments were performed at staff discretion. Two wearable-derived algorithms were evaluated: the Continuous Remote EWS (CREWS), based on a previously developed algorithm, and Remote 3 EWS (R3EWS), a modified version of the hospital’s standard MEWS using three parameters. The primary outcome was diagnostic accuracy for clinical deterioration, defined as postoperative complications graded Clavien–Dindo ≥ II. A total of 544 admissions (516 patients) were included, of which 98 admissions (18%) experienced clinical deterioration (comprising 154 clinical deterioration events). Following the transition from mandatory to discretionary nurse-measured MEWS assessment, intermittent nurse-measured vital signs were performed less frequently, while MEWS ≥ 3 occurred more often, resulting in higher MEWS sensitivity and lower specificity. In the separate diagnostic performance analysis, R3EWS showed slightly higher AUROC values (0.61) compared with MEWS (0.58) and CREWS (0.59), although differences were modest. Wearable-derived alarm frequency increased 6–8 h before clinical deterioration. In a surgical ward where continuous wearable monitoring was already available, transition from mandatory to discretionary nurse-measured MEWS assessment was associated with fewer intermittent observations, higher MEWS sensitivity, and lower specificity. Wearable-derived EWS algorithms showed comparable but modest discriminative performance relative to conventional MEWS. The increased number of alerts highlights the need for prospective validation and clear protocols for integrating continuous monitoring data into ward escalation workflows.